Genetic evaluation of survival and productivity traits in Arman crossbred sheep - Shariati, Mohammad Mahdi; Zerehdaran, Saeed; Pourbayramian, Fatemeh; Hasanvand, Shokoufeh; Mohammadi, Kourosh (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Arman sheep breed was synthesized by crossing several breeds, including Baluchi, Ghezel, Chios, and Suffolk. Objective: To estimate the (co)variance components and genetic parameters using the restricted maximum likelihood via twelve animal models for lamb survival and four animal models for ewe productivity traits. Methods: Data and pedigree information were collected at Abbasabad Sheep Breeding Station, Khorasan Razavi province, north-east of Iran, from 1999 to 2011. The traits studied were lamb survival rate (LSR), litter size at birth (LSB), litter size at weaning (LSW), litter mean weight per lambing (LMWL), litter mean weight per lamb weaned (LMWLW), total litter weight at birth (TLWB), and total litter weight at weaning (TLWW). Moreover, multivariate analyses were performed to estimate covariance between the traits. Results: Direct heritability estimates (h2a) for LSR was 0.081 and increased to 0.253 after correcting. Maternal genetic effects (h2m) and common litter effects (l2) accounted for 4 and 11.3% of the phenotypic variance for LSR, respectively. The estimations of h2a were 0.131, 0.080, 0.111, 0.190, 0.118, and 0.150 for LSB, LSW, LMWL, LMWLW, TLWB, and TLWW, respectively. The estimated fractions of variance —attributed to permanent environmental effects on ewe, (pe2) were 0.038, 0.050, 0.071, 0.060, and 0.050 for LSB, LSW, LMWL, TLWB, and TLWW, respectively. Service sire effects (S2) were significant for LSW, LMWL, and TLWB, being 0.038, 0.030, and 0.049, respectively. Direct genetic correlations showed a vast range from 0.13 for LSB-LMWL to 0.91 for LMWL-TLWW. Conclusion: Results indicate that genetic change not only depends on the heritability of traits, but also on the observed phenotypic variation; therefore, improvement of non-genetic factors should be included in the breeding programs.